A modo de epílogo. La Ría de Huelva: conclusiones y perspectívas. - Rovira, Salvador; Belén, María; Escacena, José Luis; Domínguez de la Concha, Antonio; Perea, Alicia; Ruiz- Gálvez, Marisa (Complutum, 1995)
Sin resumen